PENDAPATAN DAN HUBUNGAN PRODUKSI PEMANENAN HUTAN RAKYAT DI KECAMATAN DONRI-DONRI KABUPATEN SOPPENG - Ardianty Abbas (Jurnal Eboni, 2021)
This research aims to describe the patterns of people forest harvesting, to know the enterpreneurs income on various harvesting pattern and to know the production relationship happened in people forest harvesting. The use of this research is the information about the income influence of various patterns to the production relationship of people forest harvesting. This reseach held on May until June, 2013 in Donri-Donri Subregency, Soppeng Regency. Primary data obtained by observation and interview in the field. Data analysis done by descriptive to describe the relations of production about social relation’s production, the characteristic of relation production, and the structure of relation production. The quantitative analysis conducted by counting the revenue from each actors of harvesting. The result of this research obtained the the harvesting pattern of people forest accured in Donri-Donri Subregency. The enterpreneurs buy the wood by sortimen, by the tree and as a gatherer marketer. The biggest revenue of the enterpreneurs is buy the wood by tree. Production method held is komersialis, capitalist and subsistence production.